Comparative Assessment of Essential Elements in Populations from Saline and Treated Water Areas - Noor M. Al-Humaidy (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Safe drinking water is fundamental to human health, yet groundwater salinity in arid regions poses significant environmental health threats, particularly affecting electrolyte homeostasis and trace element status in populations relying on untreated well water. Specific Background: In southern Iraq's Al-Rifai District, Thi-Qar Province, rural communities depend on saline groundwater with elevated sodium and total dissolved solids, while urban populations consume treated municipal water with lower salinity and stable quality monitoring. Knowledge Gap: Limited biochemical data exist on how chronic saline well-water consumption affects serum concentrations of essential elements in healthy adults within this region. Aims: This study compared serum levels of iron, calcium, zinc, sodium, potassium, and magnesium between 200 rural well-water consumers and 200 urban treated-water consumers aged 20-50 years using atomic absorption spectrophotometry, Arsenazo III method, and ion-selective electrodes. Results: Rural participants showed significantly lower serum iron, zinc, calcium, magnesium, and potassium (P<0.01) but elevated sodium (P<0.01) compared to urban residents, with deficiency prevalence reaching 36% for zinc and 28% for iron in rural areas. Novelty: This investigation uniquely quantifies the environmental-biochemical linkage between groundwater salinity and essential element depletion in Iraqi populations, demonstrating freshwater salinization syndrome's impact on mineral homeostasis. Implications: Findings necessitate systematic rural water quality monitoring through Water Safety Plans, deployment of point-of-use reverse osmosis systems with remineralization, and targeted nutritional interventions to address dual environmental and nutritional burdens threatening cardiovascular and metabolic health in saline-groundwater-dependent communities.Keywords : Groundwater Salinity, Trace Elements, Serum Minerals, Well Water, Thi-Qar IraqHighlight : Rural well-water consumers showed significantly lower iron, zinc, calcium, magnesium, and potassium levels. Sodium concentrations were markedly elevated among populations drinking saline groundwater versus treated water. Chronic exposure creates dual nutritional-environmental burden requiring water quality monitoring and treatment interventions